Religion, communism, and Ratu Adil Colonialism and propaganda literature in 1920s Yogyakarta - Margana, Sri (Wacana, Journal of the Humanities of Indonesia, 2019)
This article examines the social realities of literary works and the colonial perceptions of socio-political movement inspired by the ideologies of Islam, communism, and the Just King (Ratu Adil). The main sources for this study are four propaganda literatures published by the Resident of Yogyakarta, Louis Frederik Dingemans (1924-1927). It employs post-colonial literary theory to analyse the colonial authority’s perceptions of Islam, communism, and Ratu Adil, and examines how colonial rulers (as colonizers) positioned themselves as above indigenous society (the colonized) as the guardians of moral, social, and political order.